2017
DOI: 10.1002/ece3.3690
|View full text |Cite
|
Sign up to set email alerts
|

Early phenology and growth trait variation in closely related European pine species

Abstract: Closely related taxa occupying different environments are valuable systems for studying evolution. In this study, we examined differences in early phenology (bud set, bud burst) and early growth in a common garden trial of closely related pine species: Pinus sylvestris, P. mugo, and P. uncinata. Seeds for the trial were sourced from populations across the ranges of each species in Europe. Over first 4 years of development, clear differences were observed between species, while the most significant intraspecifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(32 citation statements)
references
References 40 publications
2
30
0
Order By: Relevance
“…Two sets of populations, one including Pyrenean sites and the other composed of stands in Massif Central and Sierra de Gudar, were distinguished by the Bayesian method and multivariate tests. Further differentiation of these populations was observed in the Pyrenean cluster, with the northwestern population U23 being distinct from two Andorran sites, which was in keeping with prior observations of a significantly slower growth rate of pines in this region [22].…”
Section: Inner Genetic Variation Of Three Pine Species Populationssupporting
confidence: 88%
See 1 more Smart Citation
“…Two sets of populations, one including Pyrenean sites and the other composed of stands in Massif Central and Sierra de Gudar, were distinguished by the Bayesian method and multivariate tests. Further differentiation of these populations was observed in the Pyrenean cluster, with the northwestern population U23 being distinct from two Andorran sites, which was in keeping with prior observations of a significantly slower growth rate of pines in this region [22].…”
Section: Inner Genetic Variation Of Three Pine Species Populationssupporting
confidence: 88%
“…For the majority of statistical analyses, a closer relationship between Pyrenean pine and Scots pine was observed, rather than between the latter and dwarf pine, and the pattern was mostly affected by two Pyrenean pine populations. A close genetic relation between these taxa, which could have preserved more of the ancestral polymorphisms, was also observed in earlier comparative analyses of transcriptomes, phenology, and certain phenotypic traits (growth form and rate, needle characters [18,22,26]). Interestingly, notably more outliers were found in this instance in comparisons between Pyrenean and Scots pines than between the reference species and dwarf pine-1 and 35, respectively.…”
Section: Discrimination Of the Speciessupporting
confidence: 66%
“…Here, we describe the design and testing of a 49,829 SNP chip (Axiom_PineGAP array) for population genetic and molecular breeding studies in pines, with a focus on Scots pine (Pinus sylvestris L.), dwarf mountain pine (P. mugo T.), mountain pine (P. uncinata R.) and peat-bog pine (P. uliginosa N.). These taxa form a monophyletic group within Pinaceae, but differ strongly in phenotype, geographical distribution and ecology (Wachowiak, Perry, Donnelly, & Cavers, 2018).…”
Section: Picea Abiesmentioning
confidence: 99%
“…Here, we describe the design and testing of a 49,829 SNP chip (Axiom_PineGAP array) for population genetic and molecular breeding studies in pines, with a focus on Scots pine ( Pinus sylvestris L.), dwarf mountain pine ( P. mugo T.), mountain pine ( P. uncinata R.) and peat‐bog pine ( P. uliginosa N.). These taxa form a monophyletic group within Pinaceae, but differ strongly in phenotype, geographical distribution and ecology (Wachowiak, Perry, Donnelly, & Cavers, 2018). This, together with their recent speciation history and high phenotypic divergence, mean they are especially suitable for comparative analyses of patterns of polymorphism and divergence and form a useful experimental system for studies of phenotypic trait variation at different ecological and evolutionary timescales (Wachowiak et al, 2015; Wachowiak, Zaborowska, et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Gene flow and isolation by distance were other major factors affecting population differentiation in the Scots pine that were defined using neutral DNA markers [28]. Numerous studies based on indoor and field trials revealed a significant clinal variation among the Scots pine populations over latitude gradients in adaptive traits such as phenology [29,30].…”
Section: Introductionmentioning
confidence: 99%